Endostructural morphology in hominoid mandibular third premolars: Geometric morphometric analysis of dentine crown shape. Issue 133 (August 2019) - Davies, Thomas W.; Delezene, Lucas K.; Gunz, Philipp; Hublin, Jean-Jacques; Skinner, Matthew M.
Abstract: In apes, the mandibular third premolar (P3 ) is adapted for a role in honing the large upper canine. The role of honing was lost early in hominin evolution, releasing the tooth from this functional constraint and allowing it to respond to subsequent changes in masticatory demands. This led to substantial morphological changes, and as such the P3 has featured prominently in systematic analyses of the hominin clade. The application of microtomography has also demonstrated that examination of the enamel-dentine junction (EDJ) increases the taxonomic value of variations in crown morphology. Here we use geometric morphometric techniques to analyze the shape of the P3 EDJ in a broad sample of fossil hominins, modern humans, and extant apes ( n = 111). We test the utility of P3 EDJ shape for distinguishing among hominoids, address the affinities of a number of hominin specimens of uncertain taxonomic attribution, and characterize the changes in P3 EDJ morphology across our sample, with particular reference to features relating to canine honing and premolar 'molarization'. We find that the morphology of the P3 EDJ is useful in taxonomic identification of individual specimens, with a classification accuracy of up to 88%. The P3 EDJ of canine-honing apes displays a tall protoconid, little metaconid development, and an asymmetrical crown shape. Plio-Pleistocene hominin taxa display derived masticatory adaptations at the EDJ, such as the molarized premolars of Australopithecus africanus and Paranthropus, which have well-developed marginal ridges, an enlarged talonid, and a large metaconid. Modern humans and Neanderthals display a tall dentine body and reduced metaconid development, a morphology shared with premolars from Mauer and the Cave of Hearths. Homo naledi displays a P3 EDJ morphology that is unique among our sample; it is quite unlike Middle Pleistocene and recent Homo samples and most closely resembles Australopithecus, Paranthropus and early Homo specimens .